ANALYZING THE IMPACT OF INTEREST RATE CHANGES ON CONSUMER LOAN DEMAND AND BANK PROFITABILITY - Zaenal Aripin; Fitriana; Faisal Matriadi (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
Background:Interest rate changes represent fundamental monetary policy tools with profound implications for consumer borrowing and bank profitability through complex transmission mechanisms. Aims:This research analyzes the impact of interest rate fluctuations on consumer loan demand and bank profitability across different economic contexts. Research Method:Employing longitudinal mixed-methods design, we examined data from 25 banks over five years, incorporating quantitative lending analysis and qualitative consumer/executive insights. Results and Conclusion:1% rate increase corresponds to 12% decrease in loan applications, with mortgages most sensitive. Bank profitability shows complex relationships: 8% increase for diversified portfolios, 3% decrease for consumer-focused institutions. Contribution:The study contributes to monetary policy transmission theory and provides practical frameworks for optimizing product positioning and risk management across interest rate cycles. This study aims to analyze the effect of interest rate changes on consumer loan demand and the profitability of commercial banks. It seeks to identify patterns, establish causal relationships, and propose actionable insights for financial institutions.   Research Method: A mixed-method approach is adopted, employing both qualitative and quantitative data. Time-series analysis is conducted on historical data spanning the last two decades, incorporating macroeconomic variables and interest rate trends. In addition, surveys of consumer attitudes toward loans at different interest rate levels are analyzed to gauge demand sensitivity.   Results and Conclusion: Preliminary findings suggest a significant inverse relationship between interest rates and consumer loan demand. Banks experience increased profitability in periods of higher interest rates, although at the cost of potential market contraction. Lower rates generally boost consumer loan demand, but the effects on profitability are more nuanced, depending on the type of loan products offered.   Contribution: This research provides a comprehensive analysis of how shifts in interest rates influence consumer behavior and bank profitability. It contributes to a better understanding of how banks should tailor their lending strategies in response to rate changes and provides insights for policymakers on the broader economic implications of interest rate adjustments.